Insular glass and amber studs, seventh to twelfth century AD: dating, chronology and workshop practice - Gleeson, Jennifer M. (Trinity College (Dublin, Ireland). Department of History of Art and Architecture, 2017)
Studs of glass and amber are found alongside panels of gold filigree and embossed silver foils, are an integral part of high status Insular metalwork created between the seventh and twelfth centuries. No over-arching survey has been carried out on the materials, form, colour, and techniques employed to make such studs. While this study sets out to address this dearth of information, due to losses over time this survey cannot be definitive, what does remain provides a snapshot which may tell us something of the relationship that existed between artefacts traditionally grouped together by date or workshop tradition, or shed light on issues such as authorship or workshop practice.
Keywords: History of Art, Ph.D.; Ph.D. Trinity College Dublin, 2017